The Effect of the Agrobacterium tumefaciens attR Mutation on Attachment and Root Colonization Differs between Legumes and Other Dicots - Matthysse, Ann G. (American Society for Microbiology, 2001)
Infections of wound sites on dicot plants by Agrobacterium tumefaciens result in the formation of crown gall tumors. An early step in tumor formation is bacterial attachment to the plant cells. AttR mutants failed to attach to wound sites of both legumes and nonlegumes and were avirulent on both groups of plants. AttR mutants also failed to attach to the root epidermis and root hairs of nonlegumes and had a markedly reduced ability to colonize the roots of these plants. However, AttR mutants were able to attach to the root epidermis and root hairs of alfalfa, garden bean, and pea. The mutant showed little reduction in its ability to colonize these roots. Thus, A. tumefaciens appears to possess two systems for binding to plant cells. One system is AttR dependent and is required for virulence on all of the plants tested and for colonization of the roots of all of the plants tested except legumes. Attachment to root hairs through this system can be blocked by the acetylated capsular polysaccharide. The second system is AttR independent, is not inhibited by the acetylated capsular polysaccharide, and allows the bacteria to bind to the roots of legumes.